2016
DOI: 10.5751/es-08797-210337
|View full text |Cite
|
Sign up to set email alerts
|

The governance of adaptation: choices, reasons, and effects. Introduction to the Special Feature

Abstract: ABSTRACT. The governance of climate adaptation involves the collective efforts of multiple societal actors to address problems, or to reap the benefits, associated with impacts of climate change. Governing involves the creation of institutions, rules and organizations, and the selection of normative principles to guide problem solution and institution building. We argue that actors involved in governing climate change adaptation, as climate change governance regimes evolve, inevitably must engage in making cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 45 publications
1
82
0
10
Order By: Relevance
“…We also found that although not reaching particularly high scores, boundary experiments produced more goal convergence and understanding of mindsets than the other two types. Climate adaptation is a wicked policy issue that involves significant uncertainty and divergent framings, as well as deep uncertainty about the rate of change in the ecological system [2]. It is reasonable to assume that future solutions will require the input of many different actors and knowledges, and the combining of different understandings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that although not reaching particularly high scores, boundary experiments produced more goal convergence and understanding of mindsets than the other two types. Climate adaptation is a wicked policy issue that involves significant uncertainty and divergent framings, as well as deep uncertainty about the rate of change in the ecological system [2]. It is reasonable to assume that future solutions will require the input of many different actors and knowledges, and the combining of different understandings.…”
Section: Discussionmentioning
confidence: 99%
“…To identify solutions that work, it is suggested that policy actors employ a "learning-by-doing" approach, where an idea is executed and evaluated to understand its impacts and reduce uncertainty [1]. Climate adaptation requires the production of new knowledge to understand the impacts of climate change, new knowledge about the impacts on the ecological system of society's response to those changes, and insights into how actors perceive and understand the changes that are happening [2]. Governance systems that enable learning will make better use of this knowledge and understanding and build adaptive capacity [3], improve their decision making, and potentially enable policy change [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…More simply, this involves efforts to reduce risks and vulnerabilities expected under climate change. For example, Huitema et al (2016) place the role of creating and building institutions as a central task in climate adaptation governance but observe that "little is known about how and why these choices are made in practice, and how such choices affect the outcomes of our efforts to govern adaptation. In general, however, institutional development is typically considered to be difficult to realize and remains poorly understood.…”
Section: Climate Adaptation Governancementioning
confidence: 99%
“…extremely difficult (Dovers & Hezri, 2010;Huitema et al, 2016). Urban governance typically involves densely networked institutional arrangements and dispersed responsibility and authority, spanning multiple jurisdictional levels within and beyond the urban territory (Bulkeley & Betsill, 2013).…”
mentioning
confidence: 99%
“…Utilizing bottom-up, negotiatory processes to specify dimensions and characteristics of the urban resilience concept can be regarded as a promising strategy for reducing subjectivity. Conceptualization using negotiation-based, knowledge co-design, and co-production approaches can also facilitate operationalization of the resilience concept, including design, implementation, and monitoring stages [20].…”
Section: Introductionmentioning
confidence: 99%